2019
DOI: 10.3390/cells8070740
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Acquired Resistance towards EGFR Inhibitor Gefitinib in a Patient-Derived Xenograft Model of Non-Small Cell Lung Cancer and Subsequent Molecular Characterization

Abstract: In up to 30% of non-small cell lung cancer (NSCLC) patients, the oncogenic driver of tumor growth is a constitutively activated epidermal growth factor receptor (EGFR). Although these patients gain great benefit from treatment with EGFR tyrosine kinase inhibitors, the development of resistance is inevitable. To model the emergence of drug resistance, an EGFR-driven, patient-derived xenograft (PDX) NSCLC model was treated continuously with Gefitinib in vivo. Over a period of more than three months, three separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…These results indicated that genipin might directly bind to the STAT-3-SH2 domain and inhibit the dimerization of STAT-3 or STAT-1:STAT-3. EGFR can also bind to the STAT-3-SH2 domain and activate STAT-3 [27]. GST pull-down results indicated that purified STAT-3-SH2 interplayed with EGFR and genipin exposure (20 μM) suppressed the complex formation (Fig.…”
Section: Genipin Binds To Sh2 Domain In Stat-3mentioning
confidence: 92%
“…These results indicated that genipin might directly bind to the STAT-3-SH2 domain and inhibit the dimerization of STAT-3 or STAT-1:STAT-3. EGFR can also bind to the STAT-3-SH2 domain and activate STAT-3 [27]. GST pull-down results indicated that purified STAT-3-SH2 interplayed with EGFR and genipin exposure (20 μM) suppressed the complex formation (Fig.…”
Section: Genipin Binds To Sh2 Domain In Stat-3mentioning
confidence: 92%
“…Several studies have proved that gefitinib exerts anticancer activity in multiple types of human cancer, including non‐small cell lung cancer, and ESCC (Sasatani et al, 2019; Schueler et al, 2019; Zhang et al, 2019). But, the resistance to gefitinib treatment is a major obstacle to the effective treatment of patients with ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing numbers of in vitro and in vivo studies have reported various possible molecular mechanisms of drug resistance to gefitinib, among which EGFR gene amplification and EMT are the most studied (28)(29)(30). Rho et al reported that EMT resulting from repeated exposure to gefitinib blunted the sensitivity of A549 cells to EGFR inhibitors (31).…”
Section: Discussionmentioning
confidence: 99%